2020
DOI: 10.1177/2399654420951803
|View full text |Cite
|
Sign up to set email alerts
|

The revenge of the village? The geography of right-wing populist electoral success, anti-politics, and austerity in Germany

Abstract: This paper discusses the geography of the electoral successes of the right-wing populist party Alternative for Germany (AfD) in the national election to the German parliament in September 2017. Unlike other studies that reduce the electoral pattern to differences between “the city” and “the country,” we do not accept the empirical observation of an urban-rural divide as a sufficient explanation. By doing so, this paper proposes a theorization of the urban and the rural as social relationships that can be diale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 30 publications
0
27
0
2
Order By: Relevance
“…A comparable lean towards tolerance is also true for the lower-grade service class (192% more likely), small business owners (98% more likely), and skilled workers (40% more likely). Similarly, results from Germany indicate a visible trend towards tolerance among respondents from bigger cities, who are 31% more likely to be tolerant than rural majority respondents; this latter group have been found to be more receptive to populist parties such as the AfD (Förtner, Belina, and Naumann 2020). In terms of age, there appears to be a strong divide in attitudes towards tolerance.…”
Section: Resultsmentioning
confidence: 90%
“…A comparable lean towards tolerance is also true for the lower-grade service class (192% more likely), small business owners (98% more likely), and skilled workers (40% more likely). Similarly, results from Germany indicate a visible trend towards tolerance among respondents from bigger cities, who are 31% more likely to be tolerant than rural majority respondents; this latter group have been found to be more receptive to populist parties such as the AfD (Förtner, Belina, and Naumann 2020). In terms of age, there appears to be a strong divide in attitudes towards tolerance.…”
Section: Resultsmentioning
confidence: 90%
“…I chose to examine the neighbourhoods of Sachsendorf and Sandow in detail for two reasons: On one hand, both are attractive neighbourhoods for refugees due to low rents and have experienced rapid diversification over the last years (for a thorough analysis for the transformation of peripheral neighbourhoods in East Germany due to the arrival of refugees, see El-Kayed, Bernt, Hamann, & Pilz, 2020). On the other hand, it is those neighbourhoods where voter turnout for the far-right party Alternative for Germany (AfD) has been the city's highest, encompassing 23,6% and 26,5% respectively in 2019's municipal elections (Stadt Cottbus, 2019d; for more insights on the socio-spatial conditions of the AfD's electoral success see Förtner, Belina, & Naumann, 2020).…”
Section: A Note On Research Methodsmentioning
confidence: 99%
“…A city versus country pattern was also observed as playing a role in the support of right-wing populists in Germany. In one quantitative study, "ruralness" correlated positively with a higher number of votes for the AfD at the municipal scale in the East, but not in the West (Deppisch et al, 2019in Förtner et al 2021. A study showed that, instead of racism being the main explanation for the success of the AfD, insufficient public transportation and social infrastructures are the important reasons within small towns and villages for feeling disadvantaged in comparison to refugees, and for feeling neglected by politicians (Hillje 2018).…”
Section: Peripheralization and The Rise Of Right-wing Populismmentioning
confidence: 99%
“…The crisis of the globalized capitalist economy, which resulted in the peripheralization of rural areas and the related crisis of representative democracies, triggered rural resentment against the existing order. This resentment has manifested itself in rural support for right-wing populist parties and in grassroots nationalist movements (Mamonova et al, 2020) both in Hungary (Kovai 2018;Szombati 2018;Vigvári 2019) and in Germany (Lees 2018;Vorländer et al, 2018;Förtner et al, 2021;Schmalz et al, 2021). Left-wing populism (Goes and Bock 2017;Mouffe 2018;Förtner et al, 2021), which builds on "equality and social justice" (Mouffe, 2018: 47) and a radical democracy "in which differences are still active" but where people are united in their opposition against "forces or discourses that negate all of them" (38), has not been able so far to reach the precaritized inhabitants of peripheralized rural areas.…”
Section: Introductionmentioning
confidence: 99%